2012
DOI: 10.3390/genes3020320
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Bromodomain Proteins in Regulating Gene Expression

Abstract: Histone modifications are important in regulating gene expression in eukaryotes. Of the numerous histone modifications which have been identified, acetylation is one of the best characterised and is generally associated with active genes. Histone acetylation can directly affect chromatin structure by neutralising charges on the histone tail, and can also function as a binding site for proteins which can directly or indirectly regulate transcription. Bromodomains specifically bind to acetylated lysine residues … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
113
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(122 citation statements)
references
References 154 publications
0
113
0
2
Order By: Relevance
“…11, 12 The development of this class of inhibitors has demonstrated the potential utility of treating diseases by the disruption of the protein-protein interaction network of chromatin reader modules, and is enabling pharmacological studies into how bromodomain-containing proteins (BCPs) regulate gene transcription and cell signaling. 1, 13 …”
Section: Introductionmentioning
confidence: 99%
“…11, 12 The development of this class of inhibitors has demonstrated the potential utility of treating diseases by the disruption of the protein-protein interaction network of chromatin reader modules, and is enabling pharmacological studies into how bromodomain-containing proteins (BCPs) regulate gene transcription and cell signaling. 1, 13 …”
Section: Introductionmentioning
confidence: 99%
“…Lysine acetylation in histones and non-histone proteins (such as transcription factors) has been identified as a commonly utilized post-translational modification, allowing for widespread, dynamic, and reversible control of gene expression (15). Histone acetylation impacts gene transcription both by direct relaxation of chromatin architecture through alteration of DNA-histone interactions and by providing docking sites for recruitment and assembly of transcriptional complexes (16). Although histone acetyltransferase (HAT) enzymes deposit acetyl marks on histones, a group of conserved protein modules, bromodomains (BRDs), has evolved to bind acetyl lysine motifs, forging an essential link between chromatin modifications and transcriptional control (16 -18).…”
mentioning
confidence: 99%
“…Given the chromatin-associated nature of BRD4, it is suggestive that BRD4 is physically tethered to the RacPyV genome, establishing a strong relationship between BRD4 and the viral genome. As BRD4 binds to acetylated chromatin domains, it is also involved in regulating gene transcription (Josling et al, 2012;Mochizuki et al, 2008). To examine whether BRD4 similarly regulates expression of RacPyV genes, we inhibited BRD4 in tumour cells by treating them with the small molecule inhibitor, JQ1, which has been shown previously to inhibit BRD4.…”
Section: Brd4 Is Associated With Racpyv In Neuroglial Tumour Cellsmentioning
confidence: 99%
“…In addition, there is a growing interest in the role of the chromosome-associated bromodomain protein, BRD4. This protein is implicated in numerous cellular functions, including maintenance of stem cells (Liu et al, 2014;Rodriguez et al, 2014;Wu et al, 2015), regulation of the cell cycle (Josling et al, 2012;Mochizuki et al, 2008), tethering of persistent DNA viruses (Lin et al, 2008;You et al, 2004You et al, , 2006, and regulation of viral and host-cell gene transcription (McBride & Jang, 2013). Additionally, other investigators have identified BRD4 as a mediator of polyomaviral gene transcription and replication (Wollebo et al, 2016).…”
Section: Introductionmentioning
confidence: 99%